2003
DOI: 10.1046/j.1523-1739.2003.01431.x
|View full text |Cite
|
Sign up to set email alerts
|

A Fire‐Explicit Population Viability Analysis of Hypericum cumulicola in Florida Rosemary Scrub

Abstract: Land managers seeking to reestablish historical fire regimes need guidance on how to apply prescribed fire to promote the population persistence of endangered species. We explored extinction risks of Hypericum cumulicola, a fire‐dependent plant endemic to the Lake Wales Ridge, Florida ( U.S.A ). Stochastic and deterministic matrix population models based on six censuses ( 1994–1999 ) and data from several germination and seedling survival experiments were used to compare H. cumulicola demography and extinction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 52 publications
(103 reference statements)
4
94
0
1
Order By: Relevance
“…As fires become more frequent, deterministic and stochastic population growth rates have been observed to increase in herbaceous species (Silva et al 1991;Canales et al 1994;Caswell and Kaye 2001;Quintana-Ascencio et al 2003), as well as decline in savanna woody species (Hoffmann 1999). In addition, intermediate patterns, where the population growth rate peaks at intermediate fire frequencies, have also been documented (Gross et al 1998).…”
Section: Demographic Responses To Firementioning
confidence: 91%
“…As fires become more frequent, deterministic and stochastic population growth rates have been observed to increase in herbaceous species (Silva et al 1991;Canales et al 1994;Caswell and Kaye 2001;Quintana-Ascencio et al 2003), as well as decline in savanna woody species (Hoffmann 1999). In addition, intermediate patterns, where the population growth rate peaks at intermediate fire frequencies, have also been documented (Gross et al 1998).…”
Section: Demographic Responses To Firementioning
confidence: 91%
“…Other studies also found different optimal fire intervals for populations of shrubs, but most of them agreed that, frequent burns decrease populations of woody species (e.g. Heelemann et al 2008;Quintana-Ascencio et al 2002;Satterthwaite et al 2002).…”
Section: Population Structure and Dynamicsmentioning
confidence: 94%
“…Fire may dramatically affect population dynamics of plants (reviewed in Noble and Slatyer 1980). Indeed, for most species, population dynamics have been shown to be very different in burned and unburned sites (e.g., Silva et al 1991, Canales et al 1994, Caswell and Kaye 2001, Garnier and Dajoz 2001a, Satterthwaite et al 2002, Quintana-Ascencio et al 2003, Menges and Quintana-Ascencio 2004. Fire has been shown to increase population growth rates by increasing seed production (McConnell and Menges 2002), seed germination rates (Canales et al 1994, Menges andDolan 1998), or growth (Lamont and Wiens 2003).…”
Section: Introductionmentioning
confidence: 99%